Correlates and Predictors of Depression and Anxiety Disorders in Graduate Students - Barton, Barbara A.; Bulmer, Sandra M. (Health Educator, 2017)
Depression and anxiety are increasingly prevalent on college campuses; however, few studies have explored these disorders among graduate students. Purpose of this study was to examine prevalence, correlates and predictors of depression and anxiety among graduate students. This cross-sectional study used secondary data (N=4477) collected as part of the Healthy Minds Study. The Patient Health Questionnaire (PHQ) was used as the screening instrument. Multiple logistic regression examined the effect of demographic and social variables on the outcome of screening positive. Results showed 14.0% screened positive for depression, 9.5% for anxiety, 19.1% for either, and 4.4% for both. Depression correlates included: race/ethnicity, nationality, living situation, relationship status and finances growing up. Anxiety correlates included: sex, nationality, sexual orientation, and current finances. Validated predictors for depression were relationship status and finances growing up. Validated predictor for anxiety was identifying as lesbian, gay, bisexual, transgender or queer (LGBTQ), while being male and international status were protective. These findings suggest depression and anxiety are as prevalent among graduates as undergraduates and provide insight into the social and demographic influences of screening positive. Health educators can use these findings to inform policy and programming for graduate students that will provide an appropriate combination of services.
Keywords: Anxiety Disorders; Case Studies; Correlation; Depression (Psychology); Ethnicity; Family Income; Foreign Students; Gender Differences; Graduate Students; Health Education; Health Services; Interpersonal Relationship; Minority Groups; Money Management; Place of Residence; Predictor Variables; Race; Sexual Identity; Sexual Orientation; dept.hhs; ⛔ No DOI found